Identifying microRNAs targeting Wnt/β-catenin pathway in end-stage idiopathic pulmonary arterial hypertension - Wu, Danchen; Talbot, C. Conover; Liu, Qun; Jing, Zhi-Cheng; Damico, Rachel L.; Tuder, Rubin; Barnes, Kathleen C.; Hassoun, Paul M.; Gao, Li (Journal of molecular medicine (Berlin, Germany), 2016)
MicroRNAs (miRNAs) play important roles in the pathogenesis of pulmonary arterial hypertension (PAH). However, the pathways targeted by miRNAs in PAH have not been systematically investigated. We aim to identify dysregulated miRNAs for patients with idiopathic PAH (IPAH). miRNA profiling was performed on lung tissue total RNA from eight IPAH patients and eight control subjects. Real-time quantitative RT-PCR (qRT-PCR) was used for validation of miRNA and mRNA expression levels in 14 IPAH patients and 14 control subjects. Pathway enrichment analysis showed that Wnt/β-catenin signaling is among the top PAH-related pathways enriched in target genes of dysregulated miRNAs. We confirmed the significant increased expression levels of five miRNAs ( let-7a-5p , miR-26b-5p , miR-27b-3p , miR-199a-3p and miR-656 ) targeting major PAH-related pathways. Moreover, qRT-PCR validation of Wnt/β-catenin pathway activation indicated multiple genes including receptors ( FZD4 , FZD5 ), core molecule ( CTNNB1 ), and downstream targets ( CCND1 , VEGFA , and AXIN2 ) were significantly upregulated. The expression level of miR-199b-5p was positively correlated with patients’ hemodynamics (PVR: r = 0.522, p = 0.038) and pulmonary vascular remodeling (muscularization: r = 0.540, p = 0.021). We confirmed overexpression of miR-199b-5p in hypoxic pulmonary arterial endothelial cells that negatively regulates GSK3B expression. In summary, miRNAs influence the pathogenesis of PAH by regulating major PAH-related pathways including Wnt/β-catenin in end-stage IPAH. Key message It is the first miRNA profiling study in lung tissue from end-stage idiopathic PAH. We identified dysregulated miRNAs and major pathways (e.g., Wnt signaling) in IPAH. Levels of miRNA expression were correlated with hemodynamics and pathological changes. We observed aberrant expression of target genes in the Wnt/β-catenin pathway. miRNAs influence the pathogenesis of PAH by regulating major PAH-related pathways.